كاسیگەسی ةاصاس لەظەسهەڵذانی شۆڕشی دەظذىسی لەئێشان 6491 ز - إسماعيل، إسماعيل عبدالله; إسماعيل، نجم الدين عبدالله Ismail, Najmuldin Abdullah (جامعة صلاح الدين, 2017)
هذا الموضوع عبارة عن دراسة تاريخية حول تأثيرات السوق التجاري على الثورة الدستورية الإيرانية في عام 1906م، تناول الباحث هذه التأثيرات على السوق التجارية في هذه الفترة. عند طبقات من التجار ورجال الدين. وذلك بأسلوب علمي والأكاديمي هذه الدراسة يتكون من مقدمة وثلاثة مباحث. في هذه الدراسة يتناول الباحث التأثيرات التجارية على الثورة الدستورية في عام 1906م، وكذلك يتناول الظروف الداخلية لإيران. في الأوضاع السياسية والاجتماعية والاقتصادية في إيران قد حدث فيه تحولات ملموسة لذا ألقى الباحث في المبحث الأول الضوء على الظروف الداخلية الإيرانية في عصر قاجاري عام (1796 – 1906م). حاول الباحث في هذا المنطلق أن يبرز الظروف الداخلية في إيران وذلك في عصر قاجاري بأسلوب علمي. وقع ذلك تناول بالذكر الأحداث السياسية التي حدثت في هذه الفترة. التي كانت لها دور بارزا في إندلاع الثورة الدستورية في إيران، ثم يتناول الباحث في المبحث الثاني المؤشرات البدائية التي لها دور في إيران السوق التجاري وثورة (تبغ) وفي المبحث الثالث والأخير ذكر الباحث على السوق وتأثيرات على الثورة الدستورية الإيرانية. وفي الختام وصلت الدراسة إلى نتائج أشارت إليها في نقاط مع ملخص دراسة المادة باللغتين الكردية والإنجليزية.
This topic is a historical study about market's impact on the constitution revolt in the year 1906 in Iran. It is an attempt and a scientific work to show the market's influence during that time, also to show the impact of the social classes, merchants and clergymen on the constitution revolt in the year 1906 in Iran. This research consists of an introduction and three chapters. In this research we will more focus on market's impact on the constitution revolt in the year 1906 in Iran and included a discussing about the internal situation of Iran. Moreover, the aid reasons was mentioned which have reflection on the outbreak of the constitutions revolt in Iran. As a result of that, the political, sociological and economic situation was changed. For that purpose, in the first chapter, the internal situation in Iran during the Qajar era (1796-1906) was mentioned. In this context, we will try to show scientifically the internal situation in Iran during the Qajar era. Despite of that, we will present the political events which happened during that time. All of those events in a specific level had role on outbreak constitution revolt in Iran. In the second chapter, market and tobacco revolt was discussed. It includes showing market and starting tobacco revolt, also we mentioned the direct and indirect reason of the constitution revolt in Iran. Concentrating on the market and its effect on the constitution revolt in Iran was mentioned in the third chapter of the research. In the conclusion, we have got some outcomes which will be mentioned in some points. Also we have an abstract of the research by the Arabic and English language.
Keywords: الاسواق التجارية -- الاصلاح السياسى -- الثورة الدستورية -- المستوى الاقتصادى -- التنظيمات السياسية -- إيران